Siwa Tandawa di Padanglawas - Rita Margaretha Setianingsih (Balai Arkeologi Sumatera Utara, 2014)
AbstractBiaros in Padanglawas area have many sculpter related with Siwa God. It is shows much relief about some man or giant in different pose or in dancing poses, such as Biaro Bahal I, Biaro Tandihat I, and Biaro Pulo. A pose about traditional dance and related with Siwa as destructor, and in this present shows that dance related with some traditional dance from Papak tribe in North Sumatera. There also some evindence such as triśula, Siva Tandava pose, and story from Thilai Vanam, Nandi and Ganeśa relief showed that reliefs from some biaro are related with Siwa as Hinduism God. In order to understand Padanglawas Biaras religion background, the inductive-deductive analogy from various archaeological data might be used. The result that realize including to several dancing pose, and figuratives relief at Biara Tandihat 1 showed it is similarities to the stories about Lord Siva dance and it is cult at several place.AbstrakBiaro-Biaro di Padanglawas mempunyai banyak temuan kearcaan yang berhubungan Dewa Siwa. Itu semua memperlihatkan relief tentang orang atau raksasa dalam berbagai pose seperti di Biaro Bahal I, Biaro Tandihat I, dan Biaro Pulo. Pose yang berhubungan dengan tari tradisional dan sesuai dengan Siwa sebagai penghancur, pada saat ini ada persamaan dengan tari tradisional dari suku bangsa Pakpak di Sumatera Utara. Juga ditemukan beberapa bukti seperti triśula, beberapa pose dari Siwa Tandawa, cerita tentang Hutan Thilai, Nandi dan Ganesa, kesemuanya berhubungan dengan Dewa Siwa sebagai Dewa Agama Hindu. Untuk memahami latar belakang keagamaan di Biaro-Biaro Padanglawas, maka digunakan penalaran induktif-deduktif dari berbagai data arkeologis. Hasil yang dicapai meliputi beberapa pose tari dan relief tokoh yang ada di Biaro Tandihat I memperlihatkan kesamaan dengan cerita tarian Dewa Siwa di beberapa tempat dan adanya pengkultusan kepada Dewa Siwa.